STRATEGI PENINGKATAN KINERJA ORGANISASI RUMAH SAKIT UMUM DAERAH (RSUD) KOTA BAUBAU - Ismaniar Ismail (Program Studi Administrasi Publik, 2016)
Improved performance is done so that organizational goals can be achieved on an ongoing basis with both the organization will need to select and sort out appropriate strategies to achieve the desired performance This study aimed to analyze the organization's performance improvement strategy RSUD Baubau City. This study used a qualitative approach. Data collection pursued through observation, interviews and documentation of the informants who are directly involved in the implementation of these activities. The process of data analysis include data reduction, data presentation, and conclusion. The results showed that: Preparation of performance improvement strategy RSUD Baubau City compiled based performance management system, including performance planning, implementation, feedback / monitoring and performance evaluation. In addition, the strategy performance is also still refers to the strategic plan of the hospital. Nevertheless, the strategy was not elaborated RSUD Baubau City with more specific.